Can we identify cystic fibrosis from skeletal remains? A proposed differential diagnosis. Issue 4 (11th December 2020) - Beasley, Melanie M.; Remy, Clare K.
Abstract: Cystic fibrosis (CF) is the most common genetic disease within populations with European ancestry and affects approximately 60, 000 individuals living in North America and Europe. With recent medical advancement, the life span of CF patients has been extended by decades and bone disease has been observed as a common complication of long‐term survivors. In addition to bone disease and associated bone fracturing, living CF patients have a unique etiology of chronic sinusitis, which manifests as a medial bulge in the lateral walls of the nasal aperture, distinct from non‐CF chronic sinusitis. We suggest that available data from medical literature is sufficient evidence to indicate that CF can be identified during skeletal analysis, but future work is needed to quantify the sensitivity of the lesions for confirming a CF diagnosis.